Bioelectricity generation from human urine and simultaneous nutrient recovery: Role of Microbial Fuel Cells. (April 2022) - Sharma, Rozi; Kumari, Rekha; Pant, Deepak; Malaviya, Piyush
Abstract: Urine is a 'valuable waste' that can be exploited to generate bioelectricity and recover key nutrients for producing NPK-rich biofertilizers. In recent times, improved and innovative waste management technologies have emerged to manage the rapidly increasing environmental pollution and to accomplish the goal of sustainable development. Microbial fuel cells (MFCs) have attracted the attention of environmentalists worldwide to treat human urine and produce power through bioelectrochemical reactions in presence of electroactive bacteria growing on the anode. The bacteria break down the complex organic matter present in urine into simpler compounds and release the electrons which flow through an external circuit generating current at the cathode. Many other useful products are harvested at the end of the process. So, in this review, an attempt has been made to synthesize the information on MFCs fuelled with urine to generate bioelectricity and recover value-added resources (nutrients), and their modifications to enhance productivity. Moreover, configuration and mode of system operation, and factors enhancing the performance of MFCs have been also presented. Graphical abstract: Image 1 Highlights: Human urine is a valuable waste rich in several key nutrients. Resource recovery from urine is gaining increasing attention. Microbial fuel cells provide an alternative and novel route to valorize urine. Simultaneous electricity generation and resource recovery from urine in MFCs. Further scale-up efforts are needed to bring this technology from lab to market.